أثر الصدمات النقدية في النمو الاقتصادي للأرجنتين للمدة 1980-2018 - رفاه عدنان نجم; عبدالوهاب ذنون سعدون; أنوار سعيد ابراهيم (PROSPECTIVE RESEARCHES, 2023)
This research aims at measureing and analyzeing the impact of monetary shocks on the economic growth of the Argentine economy during the period 1980-2018, based on the hypothesis that the impact of monetary shocks is negative on the economic growth rate of the Argentine economy and this effect is clear and significant in the short term compared to the long-term, which allows to absorb the impact Cash shocks. The research uses the descriptive approach along with the standard quantitative approach to estimate and analyze the relationship between the variables of the standard model, and estimate the impact of monetary shocks on the economic growth of the sample. The research has been divided into two aspects, the first are presents the theoretical frameworks of the subject of monetary shocks as it contains the concept, types and most important causes and models addressed to measure and estimate, while the second aspect focused on the use of methods and tests of the standard model for the analysis and measurement of the relationship between the growth rate of GDP, which represented the variable as money supply, inflation, exchange rate the stability of the time series data as well as the co-integration test and the causality test between the variables of the model were used, and then Using the AutoRegressive Distributed Lag Model (Ardl) and the error correction model. The study concluded a set of results and proposals, the most important of which is to confirm the relationship of negative and moral impact of monetary shocks on the economic growth rates in Argentina during the period 1980-2018.